Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2024)
Table of Content: 1. Agile Management system role in achieving the development and creativity of employees in Industrial companies in Jordan: A field study on workers in industrial companies - Jordan 2023 Musab Abdullah Ali Alrawajfa, Safaa Mahmoud Bashir Al-Sarayrah 2. Legal adaptation of Palestinian resistance in the Gaza Strip In the light of the rules of public international law Mohamad Mahmoud Doughan 3. The impact of entrepreneurial awareness on small and medium enterprises in the light of the requirements of the national transformation program Najwa Samran Awad Alhathli 4. Governance of Endowment Institutions and Their Role in Supporting Entrepreneurial Projects in the Sultanate of Oman "An Analytical Comparative Study" Khalifa Mohammed Khalifa Al-Hamdi 5. Determinants of women’s participation in the labor force in the Arab countries - an econometric study using the Panel Data model during the period )2000-2020 ( Fatimah Fahd Alateeg, Vivian Mohammed Nasrulddin 6. The impact of organizational silence on job creativity: A field study for employees of the Ministry of National Guard: in the western sector in Jeddah Governorate SAEED AYIDH Alahmari, Dr. Kamal Nawawi Tawheed Filemban 7. The Impacts of Using Artificial intelligence on Auditors Performance in Saudi Business Environment Ms. Kawthar Ali Al-Salem 8. Effectiveness of Strategic Planning on Developing Performance in Sudanese Higher Education Institutions from Total Quality Perspective: (Case Study Sudan University of Science and Technology) Dr.Siham Haider Elderderi, Dr.Mohamed Ahmed Albadawi, Dr. Sameh Mohamed Abdelhay